A Clinical Care Pathway to Reduce ICU Usage in Head and Neck Microvascular Reconstruction. (31st July 2018) - Morse, Elliot; Henderson, Cara; Carafeno, Tracy; Dibble, Jacqueline; Longley, Peter; Chan, Edwin; Judson, Benjamin; Yarbrough, Wendell G.; Sasaki, Clarence; Mehra, Saral
Abstract : Objective: To design and implement a postoperative clinical care pathway designed to reduce intensive care usage on length of stay, readmission rates, and surgical complications in head and neck free flap patients. Methods: A postoperative clinical care pathway detailing timelines for patient care was developed by a multispecialty team. In total, 108 matched patients receiving free tissue transfer for reconstruction of head and neck defects in the year before (prepathway), year after (early pathway), and second year after (late pathway) pathway implementation were compared based on postoperative length of stay, 30‐day readmission rate, intensive care unit (ICU) admission, and rates of medical/surgical complications. Results: Median length of stay decreased from 10 to 7.5 and 7 days in the pre‐, early, and late‐pathway groups, respectively ( P =. 012). Readmission rate decreased from 16% in the prepathway group to 0% and 3% in the early and late‐pathway groups. The number of patients admitted to the ICU postoperatively decreased from 100% to 36% and 6% in the pre‐, early, and late‐pathway groups, respectively ( P =. 025). The rates of surgical and medical complications were equivalent. Discussion: This pathway effectively reduced ICU admission, length of stay, and readmission rates, without increasing postoperative complications. These outcomes were sustainable over 2 years. Implications for Practice: Free flap patients may not require routine ICU admission and may be taken off ventilatory support in the operating room. This effectively reduces costly resource use in this patient population. Similar pathways could be introduced at other institutions.